Odpowiedzi

2009-10-24T18:42:33+02:00
3√2 -4 3√2 -4 razy √3 3√6 -4 3√6 -4 - 3√6
--------- = ------------------ = ----------- = ------- = -----
√3 + 5 √3 razy √3 + 5 3 +5 8 2



7-8√ 6 7- 8√6 razy √3 7 - 8√18 7 - 8 razy 3√2 7-24√2
---------- = ------------------ = --------------- = ------------------ = ------
2√3+6 2√3+6 razy √3 2 razy3 + 6 6 + 6 12

kurcze psuje się :/ wyslę Ci na prywatnej




Najlepsza Odpowiedź!
2009-10-24T18:53:54+02:00
[3√2 -4]/[√3+5] <całość>*(√3-5) = [(3√2-4)(√3-5)] / [(√3+5)(√3-5)] = [3√6-15√2-4√3+20]/3-25=[3√6-15√2-4√3+20]/-22


[7-8√ 6]/[2√3+6] <całość> *(2√3-6)=[(7-8√6)(2√3-6)]/[12-36] = [14√3-42-16√18+48√6]/-24


[9 - √7]/[3√7+1] <całość> *(3√7-1) = [(9-√7)(3√7-1)]/[63-1] = [27√7-9-21+√7]/62= [28√7-9]/62